Is de-escalation of antimicrobials effective? A systematic review and meta-analysis. (August 2016) - Ohji, Goh; Doi, Asako; Yamamoto, Shungo; Iwata, Kentaro
Highlights: De-escalation therapy is commonly used in many clinical settings to balance clinical efficacy and the prevention of overuse of broad-spectrum antimicrobials. There is a paucity of evidence to support de-escalation, and a recent Cochrane review was not able to include any randomized controlled trials in the analysis. A systematic review and meta-analysis was conducted for various types of infection, allowing observational studies to be included in the analysis. De-escalation appeared safe and not to impair clinical effectiveness in most infections, but the quality of most of the studies included was not very high. Summary: Background: De-escalation therapy is a strategy used widely to treat infections while avoiding the use of broad-spectrum antimicrobials. However, there is a paucity of clinical evidence to demonstrate the effectiveness and safety of de-escalation therapy compared to conventional therapy. Methods: A systematic review and meta-analysis was conducted on de-escalation therapy for a variety of infections. A search of the MEDLINE (via PubMed), EMBASE, and Cochrane Library databases up to July 2015 for relevant studies was performed. The primary outcome was relevant mortality, such as 30-day mortality and in-hospital mortality. A meta-analysis was to be conducted for the pooled odds ratio using the random-effects model when possible. Both randomized controlled trials and observational studies were included in the analysis. Results: A total of 23 studies were included in the analysis. There was no difference in mortality for most infections, and some studies favored de-escalation over non-de-escalation for better survival. The quality of most studies included was not high. Conclusions: This review and analysis suggests that de-escalation therapy is safe and effective for most infections, although higher quality studies are needed in the future.